Control of Plant Viruses by CRISPR/Cas System-Mediated Adaptive Immunity - Cao, Yongsen; Zhou, Huanbin; Zhou, Xueping; Li, Fangfang (Frontiers in Microbiology, 2020)
Plant diseases caused by invading plant viruses pose serious threats to agriculture production in the world, and the antiviral engineering initiated by molecular biotechnology has been an effective strategy to prevent and control plant viruses. Recent advances in CRISPR/Cas systems-mediated DNA or RNA editing/interference in plants make them become very attractive tools applied in the plant protection field. Here, we review the development of CRISPR/Cas systems, and summarize their applications in controlling different plant DNA and RNA viruses by targeting viral sequences or susceptible host genes. We list some potential recessive resistance genes which can be utilized in antiviral breeding, and emphasize the importance and a promising perspective of recessive resistance genes-based antiviral breeding to generate transgene-free plants without development defects. Finally, we discuss the challenges and opportunities for the application of CRISPR/Cas techniques in the prevention and control of plant viruses in the field.